Roles of host proteases in the entry of SARS-CoV-2 - Alexandria Zabiegala; Yunjeong Kim; Kyeong-Ok Chang (BMC, 2023)
Abstract The spike protein (S) of SARS-CoV-2 is responsible for viral attachment and entry, thus a major factor for host susceptibility, tissue tropism, virulence and pathogenicity. The S is divided with S1 and S2 region, and the S1 contains the receptor-binding domain (RBD), while the S2 contains the hydrophobic fusion domain for the entry into the host cell. Numerous host proteases have been implicated in the activation of SARS-CoV-2 S through various cleavage sites. In this article, we review host proteases including furin, trypsin, transmembrane protease serine 2 (TMPRSS2) and cathepsins in the activation of SARS-CoV-2 S. Many betacoronaviruses including SARS-CoV-2 have polybasic residues at the S1/S2 site which is subjected to the cleavage by furin. The S1/S2 cleavage facilitates more assessable RBD to the receptor ACE2, and the binding triggers further conformational changes and exposure of the S2' site to proteases such as type II transmembrane serine proteases (TTPRs) including TMPRSS2. In the presence of TMPRSS2 on the target cells, SARS-CoV-2 can utilize a direct entry route by fusion of the viral envelope to the cellular membrane. In the absence of TMPRSS2, SARS-CoV-2 enter target cells via endosomes where multiple cathepsins cleave the S for the successful entry. Additional host proteases involved in the cleavage of the S were discussed. This article also includes roles of 3C-like protease inhibitors which have inhibitory activity against cathepsin L in the entry of SARS-CoV-2, and discussed the dual roles of such inhibitors in virus replication.